Preparation method of high biological activity brushite / β-tricalcium phosphate bone tissue engineering scaffold
Calcium permeable phosphite/β-tricalcium phosphate composite powder is prepared by mechanical mixing of malic acid modified hydroxyapatite with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, and mixed with water-soluble non-aqueous liquid phase , forming a composite slurry that can be preserved for a long time, and 3D printing and forming by extrusion at room temperature, solving the problems of high-temperature sintering, complex follow-up treatment and low biological activity during 3D printing, achieving high biological activity and bone tissue engineering scaffolds with excellent mechanical properties.
Patent Information
- Application Number
- CN202211707763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing bone tissue engineering scaffolds have problems such as high temperature sintering, complex follow-up treatment and low biological activity during 3D printing, and the application of calcium permeable phosphite systems in 3D printing is limited by excessive reaction and poor powder injectability.
Malic acid modified hydroxyapatite is used to mechanically mix with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate to prepare calcium permeable phosphite/β-tricalcium phosphate composite powder, and mix it with water-soluble non-aqueous liquid phase. , forming a composite slurry that can be preserved for a long time, and 3D printing is performed by extrusion at room temperature to avoid high-temperature sintering and the generation of cross-linking toxic substances.
The bone tissue engineering scaffold with high biological activity and excellent mechanical properties has good biomineralization ability and osteoblast activity, and the printing process is simplified, avoiding the problems of dimensional shrinkage and biological activity caused by high temperature treatment.
Smart Images

Figure HDA0004025346870000011 
Figure HDA0004025346870000021 
Figure HDA0004025346870000022
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and relates to a method for preparing a bone tissue engineering scaffold, and in particular to a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold by one-step extrusion 3D printing at room temperature. Background Art
[0002] With the aging of the population and various external factors leading to an increasing number of bone disease patients year by year, the demand for bone defect repair is increasing, so bone tissue engineering research has important value and significance. Taking advantage of the advantages of 3D printing technology, using 3D printing technology to prepare bionic artificial bones for personalized treatment will be an important development direction of orthopedics. At present, biphasic calcium phosphate, which has both good bone conduction and good mechanical properties, has received widespread attention in the field of bone defect repair materials using 3D printing technology.
[0003] According to the classification of different 3D printing technology routes, the use of laser selective sintering 3D printing technology can obtain bone engineering scaffolds with higher precision, but it requires higher costs (industrial-grade laser equipment and a large amount of bioceramic powder) and complex subsequent processing (excluding the re-sintering of low-melting-point adhesives and the isostatic pressing process to increase density). The scaffolds obtained by direct writing 3D printing with water-soluble adhesives and bioceramic powders mixed into a paste slurry often require the printed embryos to be degreased and sintered later. Such bone engineering scaffolds (CN202210018331.2) often show good mechanical properties, but due to high-temperature sintering, they will shrink in shape and size and lose the possibility of drug loading and composite active factors, resulting in low biological activity of the scaffolds. The scaffolds obtained by jet bonding and inkjet 3D printing of precursor ceramics have problems such as relatively low precision, insufficient density and more materials. The scaffolds for photocuring 3D printing using photosensitive materials, photoinitiators and dispersants composite bioceramic powders (CN201910446521.2) require a large amount of materials and a calcination post-processing process, and the residual photosensitive materials may not be calcined thoroughly enough to cause harm to the human body. For example, the photocuring ceramic bone scaffolds disclosed in CN201910446521.2 and CN201711264821.6 both require sintering to remove the embryo to obtain a dense sintered body, and there are also problems such as the subsequent high-temperature debonding residue and the inability to improve the biological activity after high-temperature sintering.
[0004] At present, it is an indisputable fact that bioactive calcium phosphate materials that are easily degradable are more conducive to tissue repair and reconstruction. Good osteoconductivity, excellent biocompatibility and faster degradation performance will enable calcium hydrogen phosphate dihydrate to gain a foothold in the field of bone tissue engineering, but it also has problems such as weak mechanical properties. In addition, there are few reports on the current status of the brushite system in 3D printing, mainly due to the fact that the reaction of generating brushite is too rapid and the injectability of the reaction powder is poor. Therefore, it is urgent to obtain a one-step extrusion 3D printing direct writing bioceramic scaffold that is free of sintering and complex processing such as cross-linking toxic substances, and has high activity and good mechanical properties. Summary of the invention
[0005] The invention provides a method for preparing a brushite / β-tricalcium phosphate bone tissue engineering scaffold with high biological activity, so as to overcome the defects of the prior art.
[0006] To achieve the above-mentioned purpose, the present invention provides a preparation method of a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which has the following characteristics: comprising the following steps: step 1, fully mixing malic acid-modified hydroxyapatite with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate to obtain a brushite / β-tricalcium phosphate composite powder; step 2, uniformly mixing the brushite / β-tricalcium phosphate composite powder obtained in step 1 with a water-soluble non-aqueous liquid phase to obtain a precursor slurry; then blending the precursor slurry with distilled water to obtain a brushite / β-tricalcium phosphate composite slurry; step 3, extruding the brushite / β-tricalcium phosphate composite slurry obtained in step 2 at room temperature and performing 3D printing to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold.
[0007] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step one, the method for modifying hydroxyapatite with malic acid is: ball-milling hydroxyapatite and malic acid solution at room temperature for 3 hours, and then drying and grinding to obtain hydroxyapatite modified with malic acid.
[0008] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein the mass ratio of malic acid to hydroxyapatite is 0.005-0.05:1; the concentration of the malic acid solution is 0.1-1wt.%, and the pH value is 7-7.5.
[0009] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step 1, the malic acid-modified hydroxyapatite, β-tricalcium phosphate and anhydrous dicalcium phosphate are mixed by ball milling, and the ball milling time is 2 hours.
[0010] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step 1, in the mixture of the malic acid-modified hydroxyapatite, β-tricalcium phosphate and anhydrous monocalcium phosphate, the malic acid-modified hydroxyapatite accounts for 5 to 40 wt.%, and the rest are β-tricalcium phosphate and anhydrous monocalcium phosphate, and the molar ratio of β-tricalcium phosphate to anhydrous monocalcium phosphate is 1:1.
[0011] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step 2, the water-soluble non-aqueous liquid phase is a mixture of one or more of ethanol, ethylene glycol, polyethylene glycol, propylene glycol, and glycerol.
[0012] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step 2, the mass ratio of the brushite / β-tricalcium phosphate composite powder to the water-soluble non-aqueous liquid phase is 1:0.15-0.55.
[0013] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step 2, the mass ratio of the distilled water to the water-soluble non-aqueous liquid phase is 0.1 to 1:1.
[0014] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step three, in 3D printing, the wire diameter of the injection extruder head is 0.4-1.6 mm, the printing layer height is 0.1-0.8 mm, the printing speed is 1-100 mm / s, and the printing pressure is 50-600 kPa.
[0015] Furthermore, the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, which may also have the following characteristics: wherein, in step three, after 3D printing, the sample is cured at a temperature of 35 to 40° C. and a humidity of 70 to 100% for 12 to 24 hours, and after curing, it is completely dried at 30 to 40° C. to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold.
[0016] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, wherein a brushite / β-tricalcium phosphate composite powder obtained by mechanically mixing malic acid chelated hydroxyapatite (HA) powder with β-tricalcium phosphate / anhydrous monocalcium phosphate (β-TCP / MCPA) is prepared, and mixed with a water-soluble non-aqueous liquid phase to prepare a brushite / β-tricalcium phosphate precursor slurry that can be stored for a long time, and the premixed brushite / β-tricalcium phosphate slurry is mixed with an appropriate amount of distilled water and then extruded in one step at room temperature for 3D printing. During the 3D printing process, water gradually replaces the water-soluble non-aqueous liquid phase, a hydration reaction occurs, and in-situ hardening is achieved, and finally a brushite / β-tricalcium phosphate bone tissue engineering scaffold is obtained. Among them, the chelated modified HA introduced in the present invention reacts with MCPA and effectively improves the mechanical properties. The introduction of a precursor slurry that can be preserved for a long time provides a new idea for the long-term preservation and convenient use of 3D printed materials; the prepared brushite / β-tricalcium phosphate composite slurry has good biological activity, and the water-soluble non-aqueous liquid used is relatively harmless to the human body and can be absorbed and degraded, so that the final printed scaffold has good biomineralization ability and better MC3T3-E1 osteoblast activity. Specifically, malic acid chelated HA is used as a reactant to react with dicalcium phosphate to form brushite, thereby constructing a new brushite / β-tricalcium phosphate system, and the water-soluble non-aqueous liquid phase added to the slurry can further adjust the coagulation time, so that the obtained system has excellent biological activity and cell activity. The beneficial effects specifically include:
[0017] 1. The slurry of the high bioactive scaffold obtained by the present invention is a mixture of malic acid-modified hydroxyapatite powder and β-TCP / MPCA, with the modified HA being the preferred reaction, which effectively improves the mechanical properties. The final scaffold physical products are β-TCP and DCPA (anhydrous calcium hydrogen phosphate), which have good osteoblast activity.
[0018] Second, the present invention uses a water-soluble non-aqueous liquid phase carrier for premixed brushite / β-tricalcium phosphate composite slurry and uses it in extrusion 3D printing, which not only solves the problem that the curing speed of HA, β-TCP and MCPA is too fast to be extruded and printed when reacting, but also makes the slurry have good injectability and fluidity, and at the same time makes the slurry have a longer storage time, and the powder is mixed more evenly, so that the printed stent wire diameter is uniform and controllable, the macropores are fully connected, and the interlayer bonding is good without collapse and cracking. Furthermore, the geometric shape and internal structure of the stent can be accurately controlled according to the needs of different patients to achieve personalized customization.
[0019] 3. The final products of the scaffold of the present invention, anhydrous calcium hydrogen phosphate (DCPA) and β-tricalcium phosphate (β-TCP), have good degradability and biocompatibility, and can give full play to the high efficiency growth promotion and good osteoconduction effect brought by the three-dimensional interconnected macropores of the scaffold itself. And the final product has excellent apatite formation ability, which is beneficial to accelerate osteogenesis and vascularization.
[0020] 4. In the present invention, both the modification of raw materials and the preparation of scaffolds are carried out in a low-temperature environment, which makes the scaffold have better mineralization ability and osteogenic activity, and the size of the scaffold after printing is not significantly changed or shrunk. Compared with the molding method of high-temperature printing and sintering after printing, it has obvious advantages of more precise size and higher biological activity. Therefore, the high-bioactivity scaffold prepared by the present invention can become a more effective bone tissue engineering scaffold. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a photograph of the brushite / β-tricalcium phosphate bone tissue engineering scaffold prepared in Example 1;
[0022] Figure 2 is an X-ray diffraction pattern of the cured product of the brushite / β-tricalcium phosphate composite slurry prepared in Example 1;
[0023] Figure 3 This is a test diagram of the injectability of the brushite / β-tricalcium phosphate composite slurry prepared in Example 3;
[0024] Figure 4 1 is a flowability test diagram of the brushite / β-tricalcium phosphate composite slurry (b) prepared in Example 4 and a composite slurry control group (a) without adding malic acid-modified hydroxyapatite;
[0025] Figure 5 is a photograph of the brushite / β-tricalcium phosphate bone tissue engineering scaffold prepared in Example 5;
[0026] Figure 6 is a scanning electron microscope image of the brushite / β-tricalcium phosphate bone tissue engineering scaffold prepared in Example 5 after being immersed in simulated body fluid for one day;
[0027] Figure 7 This is a graph showing the test results of the brushite / β-tricalcium phosphate bone tissue engineering scaffold prepared in Example 5 on the activity of mouse osteoblasts MC3T3-E1 cells. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments.
[0029] Example 1
[0030] This embodiment provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, comprising the following steps:
[0031] Step 1: Preparation of brushite / β-tricalcium phosphate composite powder:
[0032] (1) Weighing hydroxyapatite powder; preparing a 0.7 wt.% malic acid solution whose pH value is adjusted to about 7.3 with a 0.5 mol / L NaOH solution; placing the hydroxyapatite powder and the malic acid solution in a ball mill and subjecting them to ball milling modification at room temperature for 3 h, wherein the mass ratio of malic acid to hydroxyapatite is 0.025:1; separating the balls and the liquid after ball milling to obtain a modified mixed slurry; subjecting the modified mixed slurry to vacuum freeze drying at -55°C, and then grinding it uniformly with a mortar to obtain malic acid-modified hydroxyapatite.
[0033] (2) Mechanically mixing the malic acid-modified hydroxyapatite with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate by ball milling, wherein the mass proportion of the malic acid-modified hydroxyapatite is 5 / 10 / 20 / 30 / 40wt.%, and the rest is β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:1, and the ball milling time is 2 h. After ball milling, a brushite / β-tricalcium phosphate composite powder is obtained.
[0034] Step 2: Preparation of brushite / β-tricalcium phosphate composite slurry:
[0035] (1) The brushite / β-tricalcium phosphate composite powder is evenly blended with propylene glycol at a solid-liquid mass ratio of 1:0.5 to obtain a precursor slurry.
[0036] (2) Adding distilled water to the precursor slurry at a mass ratio of distilled water to propylene glycol of 0.2:1, the mixture is quickly blended to obtain a brushite / β-tricalcium phosphate composite slurry.
[0037] Step 3: One-step extrusion 3D printing at room temperature:
[0038] (1) Take the brushite / β-tricalcium phosphate composite slurry prepared in step 2, fill it into a disposable plastic injection tube and then push it out, repeat 1 to 2 times, fully exhaust the bubbles that may exist in the slurry, and then squeeze it into the injection tube of the 3D printer.
[0039] (2) Select a 0.6 mm extrusion needle, set the printing speed to 10 mm / s, the printing layer height to 0.2 mm, the printing pressure to 600 kp, and print according to the corresponding model. After printing, take out the sample, cure it at room temperature for 0.5 h, and then put it into a constant temperature and humidity chamber at 37° C. and 80% humidity for 12 hours, and then dry it for 2 hours to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold, such as Figure 1 shown.
[0040] The brushite / β-tricalcium phosphate composite slurry obtained in step 2 after curing was subjected to X-ray diffraction analysis. Figure 2 shown.
[0041] Example 2
[0042] This embodiment provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, comprising the following steps:
[0043] Step 1: Preparation of brushite / β-tricalcium phosphate composite powder:
[0044] (1) Weighing hydroxyapatite powder; preparing a 0.3 wt.% malic acid solution whose pH value is adjusted to about 7.3 with a 0.5 mol / L NaOH solution; placing the hydroxyapatite powder and the malic acid solution in a ball mill and subjecting them to ball milling modification at room temperature for 3 h, wherein the mass ratio of malic acid to hydroxyapatite is 0.015:1; separating the balls and the liquid after ball milling to obtain a modified mixed slurry; subjecting the modified mixed slurry to vacuum freeze drying at -55°C, and then grinding it uniformly with a mortar to obtain malic acid-modified hydroxyapatite.
[0045] (2) The malic acid-modified hydroxyapatite is mechanically mixed with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate by ball milling, wherein the mass proportion of the malic acid-modified hydroxyapatite is 20wt.%, the rest is β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:1, the ball milling time is 2h, and after ball milling, a brushite / β-tricalcium phosphate composite powder is obtained.
[0046] Step 2: Preparation of brushite / β-tricalcium phosphate composite slurry:
[0047] (1) The brushite / β-tricalcium phosphate composite powder is evenly blended with propylene glycol at a solid-liquid mass ratio of 1:0.5 to obtain a precursor slurry.
[0048] (2) Adding distilled water to the precursor slurry at a mass ratio of distilled water to propylene glycol of 0.4:1, the mixture is quickly blended to obtain a brushite / β-tricalcium phosphate composite slurry.
[0049] Step 3: One-step extrusion 3D printing at room temperature:
[0050] (1) Take the brushite / β-tricalcium phosphate composite slurry prepared in step 2, fill it into a disposable plastic injection tube and then push it out, repeat 1 to 2 times, fully exhaust the bubbles that may exist in the slurry, and then squeeze it into the injection tube of the 3D printer.
[0051] (2) Select a 0.6 mm extrusion needle, set the printing speed to 10 mm / s, the printing layer height to 0.2 mm, the printing pressure to 600 kp, and print according to the corresponding model. After printing, take out the sample, cure it at room temperature for 0.5 h, and then put it into a constant temperature and humidity chamber at 37° C. and 70% humidity for 12 hours, and then dry it for 2 hours to obtain the calcium phosphate / β-tricalcium phosphate bone tissue engineering scaffold.
[0052] The setting time test was performed on the brushite / β-tricalcium phosphate composite slurry prepared in step 2, the non-premixed slurry control group without using the water-soluble non-aqueous liquid phase, and the premixed slurry control group without using distilled water. Specifically, referring to the test method of ISO06876:2001 standard, the setting time of the slurry was measured using a needle penetration meter. When the test pointer failed to press into the sample surface, the setting time was recorded. The results are shown in Table 1.
[0053] Table 1 Solidification time test results
[0054] Group Solidification time (min) Premixed slurry (without distilled water) -(Not solidified) Unpremixed slurry (add equal amount of distilled water directly) 8.6 Example 2 (premixing and then adding distilled water) 49.5
[0055] As can be seen from Table 1, the brushite / β-tricalcium phosphate composite slurry using a water-soluble non-aqueous liquid phase (propylene glycol) does not harden, while the non-premixed slurry directly mixed with distilled water has a too fast curing time (8.6 min), which will result in too little time to load the slurry into a 3D printer and print it. The method of premixing first and then adding distilled water to gradually replace the non-aqueous phase can effectively extend the solidification time (49.5 minutes), leaving enough time for the 3D printing operation of the slurry.
[0056] Example 3
[0057] This embodiment provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, comprising the following steps:
[0058] Step 1: Preparation of brushite / β-tricalcium phosphate composite powder:
[0059] (1) Weighing hydroxyapatite powder; preparing a 0.5 wt.% malic acid solution whose pH value is adjusted to about 7.3 with a 0.5 mol / L NaOH solution; placing the hydroxyapatite powder and the malic acid solution in a ball mill and subjecting them to ball milling modification at room temperature for 3 h, wherein the mass ratio of malic acid to hydroxyapatite is 0.025:1; separating the balls and the liquid after ball milling to obtain a modified mixed slurry; subjecting the modified mixed slurry to vacuum freeze drying at -55°C, and then grinding it uniformly with a mortar to obtain malic acid-modified hydroxyapatite.
[0060] (2) The malic acid-modified hydroxyapatite is mechanically mixed with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate by ball milling, wherein the mass proportion of the malic acid-modified hydroxyapatite is 40wt.%, and the rest is β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:1, and the ball milling time is 2h. After ball milling, a calcium phosphate / β-tricalcium phosphate composite powder is obtained.
[0061] Step 2: Preparation of brushite / β-tricalcium phosphate composite slurry:
[0062] (1) Brushite / β-tricalcium phosphate composite powder and propylene glycol were uniformly blended at a solid-liquid mass ratio of 1:0.4 to obtain a precursor slurry.
[0063] (2) Add distilled water to the precursor slurry at a mass ratio of distilled water to propylene glycol of 0.25:1, and quickly blend the mixture to obtain a brushite / β-tricalcium phosphate composite slurry.
[0064] Step 3: One-step extrusion 3D printing at room temperature:
[0065] (1) Take the brushite / β-tricalcium phosphate composite slurry prepared in step 2, fill it into a disposable plastic injection tube and then push it out, repeat 1 to 2 times, fully exhaust the bubbles that may exist in the slurry, and then squeeze it into the injection tube of the 3D printer.
[0066] (2) Select a 0.6 mm extrusion needle, set the printing speed to 15 mm / s, the printing layer height to 0.2 mm, the printing pressure to 600 kp, and print according to the corresponding model. After printing, take out the sample, cure it at room temperature for 0.5 h, and then put it into a constant temperature and humidity chamber at 37° C. and 90% humidity for 12 hours, and then dry it for 1 hour to obtain the calcium phosphate / β-tricalcium phosphate bone tissue engineering scaffold.
[0067] The injectability test was performed on the brushite / β-tricalcium phosphate composite slurry prepared in step 2 and the composite slurry without the addition of malic acid-modified hydroxyapatite (control group). Specifically, the injectability of the slurry was determined using a medical syringe with a 1.9 mm inner diameter needle. The brushite / β-tricalcium phosphate composite slurry / composite slurry without the addition of malic acid-modified hydroxyapatite prepared in step 2 was injected into the syringe, and then the syringe was compressed with a universal material testing machine (CMT5105) at a speed of 15 mm / min until the force reached 400 N, as shown in FIG. Figure 3 Afterwards, the injectability was calculated as the ratio of the mass of cement extruded to the mass of cement initially loaded, and each group of samples was measured five times and the average value was taken. The results are shown in Table 2.
[0068] Table 2 Injectability performance test results
[0069] Group Injectability Composite slurry without addition of hydroxyapatite modified with malic acid 69.4% Brushite / β-tricalcium phosphate composite slurry of Example 3 93.7%
[0070] As can be seen from Table 2, the injectability of the brushite / β-tricalcium phosphate composite slurry with a malic acid-modified hydroxyapatite content of 40wt.% is 93.7%, while the injectability of the composite slurry without the addition of malic acid-modified hydroxyapatite (control group) is lower, only 69.4%. Therefore, the addition of malic acid-modified hydroxyapatite has a significant improvement in injectability.
[0071] Example 4
[0072] This embodiment provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, comprising the following steps:
[0073] Step 1: Preparation of brushite / β-tricalcium phosphate composite powder:
[0074] (1) Weighing hydroxyapatite powder; preparing a 0.7 wt.% malic acid solution whose pH value is adjusted to about 7.3 with a 0.5 mol / L NaOH solution; placing the hydroxyapatite powder and the malic acid solution in a ball mill and subjecting them to ball milling modification at room temperature for 3 h, wherein the mass ratio of malic acid to hydroxyapatite is 0.035:1; separating the balls and the liquid after ball milling to obtain a modified mixed slurry; subjecting the modified mixed slurry to vacuum freeze drying at -55°C, and then grinding it uniformly with a mortar to obtain malic acid-modified hydroxyapatite.
[0075] (2) The malic acid-modified hydroxyapatite is mechanically mixed with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate by ball milling, wherein the mass proportion of the malic acid-modified hydroxyapatite is 30wt.%, the rest is β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:1, the ball milling time is 2h, and the brushite / β-tricalcium phosphate composite powder is obtained after ball milling.
[0076] Step 2: Preparation of brushite / β-tricalcium phosphate composite slurry:
[0077] (1) The brushite / β-tricalcium phosphate composite powder is evenly blended with propylene glycol at a solid-liquid mass ratio of 1:0.4 to obtain a precursor slurry.
[0078] (2) Adding distilled water to the precursor slurry at a mass ratio of distilled water to propylene glycol of 0.5:1, the mixture is quickly blended to obtain a brushite / β-tricalcium phosphate composite slurry.
[0079] Step 3: One-step extrusion 3D printing at room temperature:
[0080] (1) Take the brushite / β-tricalcium phosphate composite slurry prepared in step 2, fill it into a disposable plastic injection tube and then push it out, repeat 1 to 2 times, fully exhaust the bubbles that may exist in the slurry, and then squeeze it into the injection tube of the 3D printer.
[0081] (2) Select a 0.6 mm extrusion needle, set the printing speed to 20 mm / s, the printing layer height to 0.2 mm, the printing pressure to 600 kp, and print according to the corresponding model. After printing, take out the sample, cure it at room temperature for 0.5 h, and then put it into a constant temperature and humidity chamber at 37° C. and 80% humidity for 12 hours, and then dry it for 1 hour to obtain the calcium phosphate / β-tricalcium phosphate bone tissue engineering scaffold.
[0082] The fluidity test was conducted on the brushite / β-tricalcium phosphate composite slurry obtained in step 2 and the composite slurry without the addition of malic acid-modified hydroxyapatite (control group). Specifically, 0.5-1 g of the brushite / β-tricalcium phosphate composite slurry / composite slurry without the addition of malic acid-modified hydroxyapatite was taken and placed on a 60 mm*60 mm glass sheet, and then a glass sheet of the same size was evenly placed on top of the slurry, and a 100 g weight was placed in the center of the upper glass sheet, and kept for 10 minutes. Finally, the diameter of the spread of the slurry was measured, such as Figure 4 The measurement results are shown in Table 3.
[0083] Table 3 Fluidity test results
[0084] Group Flow diameter / length (mm) Composite slurry without addition of hydroxyapatite modified with malic acid 19.8 Brushite / β-tricalcium phosphate composite slurry of Example 3 42.3
[0085] It can be seen from Table 3 that the spread diameter of the brushite / β-tricalcium phosphate composite slurry with a malic acid-modified hydroxyapatite content of 30 wt.% is 42.3 mm, while the composite slurry without the addition of malic acid-modified hydroxyapatite has poor fluidity and a spread diameter of only 19.8 mm.
[0086] Example 5
[0087] This embodiment provides a method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, comprising the following steps:
[0088] Step 1: Preparation of brushite / β-tricalcium phosphate composite powder:
[0089] (1) Weighing hydroxyapatite powder; preparing a 0.5 wt.% malic acid solution whose pH value is adjusted to about 7.3 with a 0.5 mol / L NaOH solution; placing the hydroxyapatite powder and the malic acid solution in a ball mill and subjecting them to ball milling modification at room temperature for 3 h, wherein the mass ratio of malic acid to hydroxyapatite is 0.025:1; separating the balls and the liquid after ball milling to obtain a modified mixed slurry; subjecting the modified mixed slurry to vacuum freeze drying at -55°C, and then grinding it uniformly with a mortar to obtain malic acid-modified hydroxyapatite.
[0090] (2) The malic acid-modified hydroxyapatite is mechanically mixed with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate by ball milling, wherein the mass proportion of the malic acid-modified hydroxyapatite is 40wt.%, and the rest is β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:1, and the ball milling time is 2h. After ball milling, a calcium phosphate / β-tricalcium phosphate composite powder is obtained.
[0091] Step 2: Preparation of brushite / β-tricalcium phosphate composite slurry:
[0092] (1) The brushite / β-tricalcium phosphate composite powder is uniformly blended with a non-aqueous liquid phase consisting of propylene glycol and polyethylene glycol at a solid-liquid mass ratio of 1:0.4 to obtain a precursor slurry.
[0093] (2) adding distilled water to the precursor slurry in a mass ratio of 0.25:1 to the non-aqueous liquid phase composed of propylene glycol and polyethylene glycol, and quickly blending the mixture to obtain a brushite / β-tricalcium phosphate composite slurry.
[0094] Step 3: One-step extrusion 3D printing at room temperature:
[0095] (1) Take the brushite / β-tricalcium phosphate composite slurry prepared in step 2, fill it into a disposable plastic injection tube and then push it out, repeat 1 to 2 times, fully exhaust the bubbles that may exist in the slurry, and then squeeze it into the injection tube of the 3D printer.
[0096] (2) Select a 0.7 mm extrusion needle, set the printing speed to 16 mm / s, the printing layer height to 0.2 mm, the printing pressure to 600 kp, and print according to the corresponding model. After printing, take out the sample, cure it at room temperature for 1 hour, and then put it into a constant temperature and humidity chamber at 37° C. and 90% humidity for 16 hours, and then dry it for 3 hours to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold, such as Figure 5 shown.
[0097] The brushite / β-tricalcium phosphate bone tissue engineering scaffold was immersed in simulated body fluid (Kokubo T, Takadama H. How useful is SBF in predicting in vivo bone bioactivity? [J]. Biomaterials, 2006, 27(15): 2907-2915.) for one day, and then taken out and its surface was characterized by SEM photography. The results are as follows: Figure 6 shown.
[0098] The brushite / β-tricalcium phosphate bone tissue engineering scaffold was placed in a 24-well plate, and the logarithmic growth phase MC3T3-E1 cells were adjusted to a density of 1×10 4 / ml, the inoculation volume was 500μL / well, 3 replicate wells and controls were set up, and the distribution of cytoskeletal protein β-action in cells was observed by immunofluorescence after 24 hours. Figure 7 shown.
[0099] from Figure 6 and 7 It can be seen that the size of the obtained scaffold is controllable, and a spherical apatite-like morphology is rapidly generated on the surface after being immersed in simulated body fluid. The morphological results of co-culture of MC3T3-E1 cells indicate that the scaffold has excellent biological activity.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold, characterized in that: The following steps are involved: Step 1: fully mixing the hydroxyapatite modified with malic acid with β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate to obtain a brushite / β-tricalcium phosphate composite powder; The method for modifying hydroxyapatite with malic acid is as follows: ball milling hydroxyapatite and malic acid solution for 3 hours at room temperature, and then drying and grinding to obtain hydroxyapatite modified with malic acid; Step 2: uniformly mixing the brushite / β-tricalcium phosphate composite powder obtained in step 1 with a water-soluble non-aqueous liquid phase to obtain a precursor slurry; and then blending the precursor slurry with distilled water to obtain a brushite / β-tricalcium phosphate composite slurry; Step 3: The brushite / β-tricalcium phosphate composite slurry obtained in step 2 is extruded and 3D printed at room temperature in one step to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold.
2. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, The mass ratio of malic acid to hydroxyapatite is 0.005-0.05:1; The concentration of the malic acid solution is 0.1~1wt.%.
3. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step 1, the malic acid-modified hydroxyapatite, β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate are mixed by ball milling for 2 hours.
4. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step 1, in the mixture of the malic acid-modified hydroxyapatite, β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, the malic acid-modified hydroxyapatite accounts for 5-40wt.%, and the rest are β-tricalcium phosphate and anhydrous calcium dihydrogen phosphate, and the molar ratio of β-tricalcium phosphate to anhydrous calcium dihydrogen phosphate is 1:
1.
5. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step 2, the water-soluble non-aqueous liquid phase is a mixture of one or more of ethanol, ethylene glycol, polyethylene glycol, propylene glycol, and glycerol.
6. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step 2, the mass ratio of the brushite / β-tricalcium phosphate composite powder to the water-soluble non-aqueous liquid phase is 1:0.15-0.
55.
7. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step 2, the mass ratio of the distilled water to the water-soluble non-aqueous liquid phase is 0.1-1:
1.
8. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step three, in 3D printing, the wire diameter of the injection extruder is 0.4~1.6mm, the printing layer height is 0.1~0.8mm, the printing speed is 1~100mm / s, and the printing pressure is 50~600kpa.
9. The method for preparing the highly bioactive brushite / β-tricalcium phosphate bone tissue engineering scaffold according to claim 1, characterized in that: in, In step three, after 3D printing, the sample is cured at a temperature of 35-40°C and a humidity of 70-100% for 12-24 hours. After curing, it is completely dried at 30-40°C to obtain a brushite / β-tricalcium phosphate bone tissue engineering scaffold.
Citation Information
Patent Citations
A method for fabricating ceramic bone scaffolds based on photopolymerization 3D printing
CN109865157B
Formula and preparation method of photocuring 3D printing haversian system artificial bone scaffold
CN110038158A
3D Printing-Based Preparation Process of Controllable Porous Bioceramic Bone Repair Materials
CN114195508B
Preparation method of bone cement catalytically cured by acidic HA (hydroxyapatite)
CN105327395A